2023
DOI: 10.3390/ijms24043810
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Interleukin-20 in Different Stages of Osteoclast Differentiation and Its Osteoimmune Regulation during Alveolar Bone Remodeling

Abstract: Osteoimmunology mediators are critical to balance osteoblastogenesis and osteoclastogenesis to maintain bone homeostasis. A lot of the osteoimmunology mediators are regulated by interleukin-20 (IL-20). However, little is known about the role of IL-20 in bone remodeling. Here, we showed that IL-20 expression was correlated with osteoclast (OC) activity in remodeled alveolar bone during orthodontic tooth movement (OTM). Ovariectomize (OVX) in rats promoted OC activity and enhanced IL-20 expression, while blockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Corroborating the findings of the present systematic review, in-vitro studies have shown that alendronate, 24 clodronate, 25 and risedronate 20 decreased osteoclast differentiation. In addition, studies have already suggested the interference of bisphosphonates (but not risedronate) in human periodontal fibroblasts after mechanical load.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Corroborating the findings of the present systematic review, in-vitro studies have shown that alendronate, 24 clodronate, 25 and risedronate 20 decreased osteoclast differentiation. In addition, studies have already suggested the interference of bisphosphonates (but not risedronate) in human periodontal fibroblasts after mechanical load.…”
Section: Discussionsupporting
confidence: 87%
“… 17 - 19 Bisphosphonates have an inhibitory effect on bone resorption and are successfully administered for the treatment of osseous disorders, such as osteoporosis. 9 , 18 , 20 Even though the action of bisphosphonate is generally well described in the literature and the effects in human subjects have also been documented, 21 - 23 studies that specifically evaluate risedronate intake and its impact on orthodontic tooth movement in humans are scarce. Although the results from this study are from animal research, and should thus be viewed with caution, the clinician should nevertheless be aware of the effects of risedronate during alveolar bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Meng et al discovered that IL-20 acted synergistically with RANKL to activate downstream signaling pathways, promoting NFATc1 expression and osteoclast formation. This effect was reversed by IL-20 inhibitors as it inhibited the interaction between RANKL and IL-20 (Meng et al 2023 ). Furthermore, Tran et al found that Rab11b reduced the surface abundance of RANK on osteoclast precursor cells and weakened NFATc1 activation, suggesting that Rab11b could serve as an inhibitor of osteoclast formation (Tran et al 2020 ).…”
Section: The Rankl/rank Signaling Pathway Activates Nfatc1mentioning
confidence: 99%
“…Yu-Hsiang Hsu, Ruey-Mo Lin et al found that in ammation, chemotaxis, matrix degradation and angiogenesis after disc herniation were affected by hypoxia conditions and controlled by IL-1, and BMP-2[19]. Bowen Meng et al found that IL-20 may be involved in osteoclast differentiation through synergistic interaction with RANKL[20]. Yuanbo Liu, and others nd IL − 20 through RANKL/nf-kappa B/NFATc1 signaling pathways increase osteoclast formation and osteoclast mediated bone erosion.Inhibition of IL-20 can effectively inhibit osteoclast differentiation and reduce bone resorption[21].…”
mentioning
confidence: 99%